Arthroscopic Bankart Repair with Remplissage: An Approach for Off-track Hill–Sachs Lesion - Sai Vineet Damodar P; Suresh Perumal; Jeganathan Parthiban; Sanjay AK; Rohit KR; Abrar H Mekkamannil (Journal of Orthopedics and Joint Surgery)
Purpose: To assess the clinical outcome and shoulder stability of Arthroscopic Bankart repair done with Remplissage in patients diagnosed with Bankart lesion and off-track Hill–Sachs lesions. Materials and methods: Thirty patients (5 females, 25 males) who presented with anterior shoulder instability and were diagnosed with Bankart lesion with off-track Hill–Sachs lesion underwent Arthroscopic Bankart repair and Remplissage. Glenoid bone loss was measured using three-dimensional computed tomography (CT) imaging, and the Hill–Sachs interval was measured to find out if the defect was on-track or off-track. Functional outcomes were assessed using DASH score, Constant–Murley score, and Rowe score prior to surgery and at 6 months and 1 year postsurgery. Results: Patients demonstrated statistically significant improvements in all scores at both 6 months and 1 year postsurgery compared with values assessed preoperatively (p < 0.001). The average DASH score improved from 45.2 before surgery to 18.4 at 1 year postsurgery. The average Constant–Murley score improved from 51.6 to 88.9, and the average Rowe score improved from 37.8 to 91.4. Conclusion: Arthroscopic Bankart repair with Remplissage is an effective and safe procedure for managing Bankart lesion with off-track Hill–Sachs defect, leading to significant improvements in functional outcomes and shoulder stability at 1 year postoperatively.